2010
DOI: 10.1021/ja1027502
|View full text |Cite
|
Sign up to set email alerts
|

Voltage-Responsive Vesicles Based on Orthogonal Assembly of Two Homopolymers

Abstract: Two end-decorated homopolymers, poly(styrene)-beta-cyclodextrin (PS-beta-CD) and poly(ethylene oxide)-ferrocene (PEO-Fc), can orthogonally self-assemble into a supramolecular diblock copolymer (PS-beta-CD/PEO-Fc) in aqueous solutions based on the terminal host-guest interactions. These assemblies can further form supramolecular vesicles, and their assembly and disassembly behaviors can be reversibly switched by voltage through the reversible association and disassociation of the middle supramolecular connectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
369
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 493 publications
(376 citation statements)
references
References 24 publications
2
369
0
Order By: Relevance
“…[1][2][3][4] Theoretical work has shown that the domain size and morphology of the phase-separated structures critically depend on the strength of the interpolymer noncovalent interactions. [5][6][7][8][9][10] To achieve these attractive enthalpic interpolymer interactions, end-functionalized homopolymers have been prepared with functional groups capable of noncovalent assembly such as hydrogen bonding, [11][12][13][14][15][16][17][18][19][20] ionic, 21 transition-metal, 22,23 host-guest, [24][25][26] and fluorophilic 27 interactions. Typically, these functional groups are attached to a homopolymer via a short, aliphatic spacer.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Theoretical work has shown that the domain size and morphology of the phase-separated structures critically depend on the strength of the interpolymer noncovalent interactions. [5][6][7][8][9][10] To achieve these attractive enthalpic interpolymer interactions, end-functionalized homopolymers have been prepared with functional groups capable of noncovalent assembly such as hydrogen bonding, [11][12][13][14][15][16][17][18][19][20] ionic, 21 transition-metal, 22,23 host-guest, [24][25][26] and fluorophilic 27 interactions. Typically, these functional groups are attached to a homopolymer via a short, aliphatic spacer.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have explored the triggered release of nanoparticles mediated by an electric field [28,29]. In this study, we developed electroresponsive nanoparticles and demonstrated that the triggered-release of PHT from our system was sensitive to an electric field in vitro (as fast as 1 min).…”
Section: Discussionmentioning
confidence: 83%
“…In particular, they cause the movement of charged molecules. Furthermore, additional transmembrane voltage can puncture cell membranes and thus increases the permeability of drugs [67]. For instance, Weaver and coworkers developed an electrically controlled drug delivery system that is based on GO nanosheets incorporated into a conducting polymer film, and found that the amount of drug released is linearly related to the time of voltage [42].…”
Section: Exogenous Stimuli-responsive Drug Deliverymentioning
confidence: 99%